Pengaruh Pengetahuan Investasi Dan Kemajuan Teknologi Terhadap Minat Generasi Z Dalam Berinvestasi Di Pasar Modal Syariah - Novita Aulia; Efni Anita; Neneng Sudharyati (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The research results show that investment knowledge (X1) has a significant positive effect on investment interest (Y). This is proven by carrying out statistical tests which produce a significant value of Tcount 5.782 > Ttable 1.662 and a sig value of 0.000 < 0.05, which means that H0 is rejected and Ha is accepted. Technological progress (X2) shows that there is a significant positive influence on investment interest (Y). This is proven by the value of tcount > ttable of 7.988 > 1.662 with a significant value of 0.000 < 0.05. So it can be concluded that H0 is rejected and Ha is accepted. Investment knowledge and technological advances together have a significant influence on investment interest. This is known by the significant value for (X1) and (X2) simultaneously having an effect on (Y) of 0.000 < 0.05 and the value of fcount > ftable (99.240 > 3.100). The coefficient of determination shows that the influence of the independent variables (X1) and (X2) on (Y) has an influence of 68.3% and the remaining 31.7% is influenced by other variables outside that were not examined in this research. So it can be concluded that Ha is accepted and H0 is rejected. This means that the higher the investment knowledge and technological advances, the higher the student's interest in investing